Konflik Batin Tokoh Utama Dalam Novel Sebening Syahadat Karya Diva SR: Kajian Psikologi Sastra Sebagai Alternatif Bahan Ajar Di SMA - Ashif Barchiya; Sri Suciarti; Siti Fatimah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The inner conflict of the main character in the novel entitled Sebening Syahadat by Diva Sinar Rembulan is interesting to research through the study of literary psychology. The inner conflict experienced by the main character in the novel begins when the main character finds the woman of his dreams and searches for an identity that he has not yet believed in. The aim of this research is to describe the inner conflict experienced by the main character of the novel Sebening Syahadat by Diva Sinar Rembulan. This type of research is a literature study. The approach used is a literary psychology approach. The method used is a qualitative method. The data collection technique used is a documentation technique in three ways, namely, literature study, reading technique, and note-taking technique. The instrument used is a data card for the classification of intrinsic elements and forms of inner conflict. The analysis technique used is content analysis technique. The presentation of the results of data analysis is carried out descriptively. The results of this research found intrinsic elements in the form of characters and characterization, plot and setting. The second thing was found to be 47 data on the form of inner conflict in the form of (6) anxiety, (1) obsession, (3) frustration, (12) guilt, (7) hurt, (1) fear, (5) inability, (12) angry. This research can be used as an alternative teaching material at the high school/vocational school level.